2017
DOI: 10.3324/haematol.2017.172353
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of continuous high-dose lenalidomide, sequential azacitidine and lenalidomide, or azacitidine in persons 65 years and over with newly-diagnosed acute myeloid leukemia

Abstract: Therapy of acute myeloid leukemia in older persons is associated with poor outcomes because of intolerance to intensive therapy, resistant disease and co-morbidities. This multi-center, randomized, open-label, phase II trial compared safety and efficacy of three therapeutic strategies in patients 65 years or over with newly-diagnosed acute myeloid leukemia: 1) continuous high-dose lenalidomide (n=15); 2) sequential azacitidine and lenalidomide (n=39); and 3) azacitidine only (n=34). The efficacy end point was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…After exclusion, based on title and abstract, 21 full-text articles were reviewed and eleven observational studies were included. 18 20 , 25 32 Screening of the reference lists for additional studies or referring articles did not yield any further articles for inclusion. Figure 1 shows a flowchart for study selection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After exclusion, based on title and abstract, 21 full-text articles were reviewed and eleven observational studies were included. 18 20 , 25 32 Screening of the reference lists for additional studies or referring articles did not yield any further articles for inclusion. Figure 1 shows a flowchart for study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 407 participants took part in the eleven trials included in this meta-analysis. 18 20 , 25 32 The studies included in this meta-analysis showed high variability in terms of the number of AML patients, ranging from 18 to 66. The median age for AML patients in these studies ranged from 63 to 76 years with the proportion of women ranging from 33% to 57%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Recently, the combination treatment of a hypomethylating agent and lenalidomide was reported in AML. 8 In a randomized 3-arm study, lenalidomide was administered at a high dosage as monotherapy (50mg/day for 28 days in the first 2 cycles) or sequentially to azacytidine. Again, poor tolerability and low efficacy was reported in this elderly population with newly diagnosed AML.…”
mentioning
confidence: 99%
“…Marie Luise Hütter-Krönke, 1 Walter Fiedler, 2 Andrea Kündgen, 3 Jürgen Krauter, 4,7 Marie von Lilienfeld-Toal, 5,8…”
unclassified